Prevention and control measures for coastal erosion in northern high-latitude communities: a systematic review based on Alaskan case studies. (19th August 2020) - Liew, Min; Xiao, Ming; Jones, Benjamin M; Farquharson, Louise M; Romanovsky, Vladimir E
Abstract: Erosion along high-latitude coasts has been accelerating in recent decades, resulting in land loss and infrastructure damage, threatening the wellbeing of local communities, and forcing undesired community relocations. This review paper evaluates the state of practice of current coastal stabilization measures across several coastal communities in northern high latitudes. After considering global practices and those in northern high latitude and arctic settings, this paper then explores new and potential coastal stabilization measures to address erosion specific to northern high-latitude coastlines. The challenges in constructing the current erosion control measures and the cost of the measures over the last four decades in northern high-latitude regions are presented through case histories. The synthesis shows that among the current erosion controls being used at high latitudes, revetments built with rocks have the least reported failures and are the most common measures applied along northern high-latitude coastlines including permafrost coasts, while riprap is the most common material used. For seawalls, bulkheads, and groin systems, reported failures are common and mostly associated with displacement, deflection, settlement, vandalism, and material ruptures. Revetments have been successfully implemented at sites with a wide range of mean annual erosion rates (0.3–2.4 m/year) and episodic erosion (6.0–22.9 m) due to the low costs and easy construction, inspection, and decommissioning. No successful case history has been reported for the non-engineered expedient measures that are constructed in the event of an emergency, except for the expedient vegetation measure using root-wads and willows. Soft erosion prevention measures, which include both beach nourishment and dynamically stable beaches, have been considered in this review. The effectiveness of beach nourishment in Utqiaġvik, Alaska, which is affected by permafrost, is inconclusive. Dynamically stable beaches are effective in preventing erosion, and observations show that they experience only minor damages after single storm events. The analysis also shows that more measures have been constructed on a spit (relative to bluffs, islands, barrier islands, and river mouths), which is a landform where many Alaskan coastal communities reside. The emerging erosion control measures that can potentially be adapted to mitigate coastal erosion in high-latitude regions include geosynthetics, static bay beach concept, refrigerating techniques, and biogeochemical applications. However, this review shows that there is a lack of case studies that evaluated the performance of these new measures in high-latitude environments. This paper identifies research gaps so that these emerging measures can be upscaled for full-scale applications on permafrost coasts.